Penilaian Postur Kerja dengan Metode REBA pada UD. Bintang Terang Roti Ketawa - Marpaung, Tommy Abadi Putra; Syarif, Abdul Azis; marpaung, tommy (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This research aims to determine the level of complaints felt by workers at UD. Bintang Terang Roti Ketawa, because there is the use of manual tools and a mismatch between body dimensions and the facilities used by the workers, seen from the results of the body map questionnaire that was distributed, there are many complaints felt by the workers, therefore the researchers identified body posture problems using the REBA method, from the assessment of the results using the REBA method obtained very high results or it was said that repairs were carried out immediately. Repairs or design of work facilities were carried out using anthropometric data of workers with normality test calculations, data adequacy, and uniformity so that the results obtained were in accordance with the dimensions of the workers' bodies, the results of facility design. The work succeeded in reducing the level of complaints felt by workers so that the design was suitable for use. Keywords: Anthropometrics, REBA, UMKM, Work Facilities